Sexual Educationin the Brazilian Common National Curricular Base: an analysis through the competences of the field of Natural Sciences - Feitosa, Raphael Alves; Praciano, Jaírla Aires; Avila, Milena Aires de (Revista de Estudios y Experiencias en Educación, 2022)
The aim of this paper is to describe how the Brazilian Common National Curriculum Base (BNCC, Portuguese acronym) approaches the issue of sexual education in the area of natural sciences. To this end, the methodology used is a document analysis consisting of the investigation of versions of the BNCC and official documents related to Brazilian education. Considering the importance that the curriculum represents for society, there is a need for debate on a national document that fulfils the role of guiding the basic knowledge which is essential for children and teenagers’ learning. This article focuses, particularly, on political issues of curricula framework that are embodied in the designing of BNCC through a qualitative method and through documentary sources. As a basic result, there were few competences that addressed sexuality in Brazilian BNCC, yet in a reductionist way, limiting sexuality to aspects of human anatomy and physiology.